Effect Of Inbreeding And Some Other Factors On Breeding Efficiency In Gir Cows - Tomar, S. S.; Kumar , Amit; Sharma , Harish (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Effects of period and season of first calving, sire and inbreeding on breeding efficiency by Wilcox (BEW) and Tomar (BET) methods were studied on 188 Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy farm, Kasturbagram, Indore (M.P.). The least squares means of BEW and BET were found to be 79.29±1.10 and 67.12±0.85 per cent, respectively. Significant effect of sire (P
Keywords: Gir cattle; Inbreeding; breeding efficiency